(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Based on an integrative approach, the aim is to demonstrate the connection between the knowledge, skills, and competencies acquired by 6th-grade students and their daily lives through lessons and extracurricular activities. This involves conducting educational research, performing experiments, fostering creativity aimed at project development, and cultivating students’ interest in creating innovations.